Penerapan model cooperative learning tipe teams games tournament (tgt) terhadap kemampuan penalaran matematika siswa pada pembelajaran matematika - Ade Sudarna; Abdul Rosyid; Ricki Yuliardi (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2018)
Students' mathematical reasoning in mathematics learning in Class VIII SMPN 1 Cibeureum of Kuningan Regency is still low. This is because the implementation of conventional learning model that less develop the ability to learn and build individuals. Conventional learning tends to minimize student involvement so teachers seem to be more active. The habit of being passive in the learning process can cause most students to be afraid and embarrassed to ask the teacher about the less interesting material. One of the learning model that is tried through this research is Teams Games Tournament (TGT) learning model. The problems in this research are: